INTRODUCTION OF A SINGLE AGRICULTURAL TAX IN TURKISTAN: PROBLEMS AND SOLUTION (Scientific journal of the Fergana State University, 2023)
This article is about the political tax  which was used in the Soviet government’s agriculture. Some facts are carried out based on the archive sources about social state of Turkestan.